2023
DOI: 10.1108/hff-02-2023-0089
|View full text |Cite
|
Sign up to set email alerts
|

Second law and thermal analyses of non-Newtonian nanofluid double-diffusive natural convection within a two-hot-baffles-equipped C-shaped domain impacted by magnetic field

Kashif Irshad,
Amjad Ali Pasha,
Mohammed K. Al Mesfer
et al.

Abstract: Purpose The entropy and thermal behavior analyses of non-Newtonian nanofluid double-diffusive natural convection inside complex domains may captivate a bunch of scholars’ attention because of the potential utilizations that they possess in modern industries, for example, heat exchangers, solar energy collectors and cooling of electronic apparatuses. This study aims to investigate the second law and thermal behavior of non-Newtonian double-diffusive natural convection (DDNC) of Al2O3-H2O nanofluid within a C-sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…They observed that thermal irreversibility declines because of the magnetic effect. Recently, Irshad et al (2024) analyzed the EG of the double-diffusive free convective flow through the non-Newtonian nanofluid in a complex domain with a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that thermal irreversibility declines because of the magnetic effect. Recently, Irshad et al (2024) analyzed the EG of the double-diffusive free convective flow through the non-Newtonian nanofluid in a complex domain with a magnetic field.…”
Section: Introductionmentioning
confidence: 99%